Past, Present and Future of Membrane Technology in Spain - Calvo, José I.; Casado-Coterillo, Clara; Hernández, Antonio (Membranes (Basel), 2021)
The following review aims at analyzing the contribution of Spanish researchers to membrane science and technology, with a historical compilation of the main milestones. We used a bibliometric analysis based on the Scopus database (1960–2020) dealing with 8707 documents covering the different disciplines and subject areas where membranes are involved. Furthermore, the information has been updated to the present moment of writing this manuscript in order to include the latest research lines and the different research groups currently active in Spain, which may lead the way to the development of the field in the coming years.